Characterisation of patients with and without cardiac magnetic resonance imaging abnormalities presenting with myocardial infarction with non-obstructive coronary arteries (MINOCA). Issue 7 (2nd November 2021) - Tayal, Bhupendar; Freeman, Phillip; Ericsson, Filip; Kragholm, Kristian Hay; Andersen, Niels Holmark; Hagendorff, Andreas; Aaroe, Jens; Sogaard, Peter; Zaremba, Tomas
Abstract: Objective: The objective of the current study is to determine the characteristics of myocardial infarction with non-obstructive coronary arteries (MINOCA) patients with and without cardiac magnetic resonance (CMR) abnormalities. Methods: We evaluated patients admitted with a presentation of acute myocardial infarction (MI) with no coronary obstruction on invasive angiography in our institution between 2012 and 2017. Patients with prior cardiac disease, myocarditis, Takotsubo cardiomyopathy and type 2 myocardial infarction were excluded. Myocardial fibrosis was determined by late gadolinium enhancement (LGE). Patients were divided into two groups based on the presence or absence of CMR abnormalities (LGE or oedema). Major adverse cardiovascular events (MACE) were defined as non-fatal MI, all-cause mortality, ventricular arrythmias or heart failure hospitalisation at follow-up. Results: Thirty-four patients fulfilling the inclusion criteria were identified. Myocardial changes with CMR were observed in 20 (59%) patients with signs of subendocardial infarct by LGE in 13 (38%) patients, transmural infarct by LGE in 6 (18%) patients and one patient had myocardial oedema. ECG and echocardiographic features were similar between patients with and without CMR abnormalities. Troponin T was significantly higher among patients with CMR abnormalities. The median duration of follow-up was 702 (IQR 456–1394) days. Two patients had MACE (both heart failure). One of them had LGE changes. Conclusions: A significant number of patients with MINOCA have ischaemic LGE changes or myocardial wall oedema. The patients with CMR abnormalities have similar ECG and echocardiographic features except higher biomarker, highlighting the role of CMR in patients with MINOCA.